Evaluasi Keberhasilan Kebuntingan Pada Sapi Madura Melalui Metode Kawin Alam: Evaluation of the success of pregnancy in Madura cattle through the natural mating method - Wulansari, Wahyuni Indah; Dwi Kusumawati, Enike; Khosiya Robba, Dewi; Chanafi, Mochammad; Ramsiati, Dyah Tuwi; Nugroho Krisnaningsih, Aju Tjatur; Ariyanti, Rina (Fakultas Peternakan Universitas Jambi, 2023)
The aim of this research is to determine the success of pregnancy in Madurese cattle using natural mating methods. The material used in this research was 36 female Madurese cattle and 3 male Madurese cattle. The research method used was field research by examining pregnancy and observing whether there was recurrent heat in cows that had been mated. The variables used in this research are Non Return Rate (NRR), Conception Rate (CR) and Service per Conception (S/C). Analysis of the data obtained was analyzed descriptively and discussed and compared with the literature. The research results showed that the percentage in Non Return Rate (NRR) for group A was 66.667%; group B 58.333% and group C 33.333%. The percentage of Conception Rate (CR) in group A was 66.667%; group B 58.333% and group C 33.333%. The Service per Conception (S/C) figure for group A was 1.5; group B 1.7 and group C 3. The percentage of Non Return Rate (NRR) for groups A and B meets the normal value, namely 66.667%, while group C is below the normal value of 33.333%. The Conception Rate (CR) percentage for groups A and B still meets the normal value, namely 66.667%, while group C is below the normal value of 33.333%. From the research results, it can be concluded that overall the evaluation of pregnancy in Madurese cattle using the natural mating method at the Beef Cattle Research Workshop is still in accordance with existing standards, this is a common occurrence in Indonesia which is adapted to natural conditions, livestock distribution and Â livestock management.